THE SEVEN HABITS OF GREAT INDONESIAN CHILDREN (SHGIC) MODEL AND ITS ROLE IN HEALTH LITERACY OF FIFTH GRADE ELEMENTARY SCHOOL STUDENTS IN DKI JAKARTA - Edwita, Edwita; Hasanah, Uswatun; Januar, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low health literacy of elementary school students in DKI Jakarta, which affects their clean and healthy living behaviors. The study aims to evaluate the effectiveness of the 7 Habits of Great Indonesian Children model in enhancing the health literacy of fifth-grade students. The method used is a quasi-experiment involving two experimental classes and two control classes. The research instrument includes a health literacy test on four indicators: access, understanding, assessment, and application. The results of the analysis showed a significant difference between the experimental and control groups (p < 0.05) with a high N-gain increase (0.65) in the experimental group. The largest increase occurred in the assessment aspect, reflecting that students' health literacy has reached the assessment stage. The implication is that this model is effective in fostering a character-based, healthy lifestyle and can be integrated into basic education to support the achievement of SDGs 3 and 4.